Party politics: An exploration of Cape Town queer nightlife and what it reveals about the politics of space and identification in post-apartheid South Africa - Meyer, Simonn (Stellenbosch : Stellenbosch University, 2022)
Thesis (MA)--Stellenbosch University, 2022.